On the identity of Ischaemum copeanum Sreek. et al. and Ischaemum keralensis Sreek. et al. (Poaceae) from Kerala, India - Ravi, N.; Mohanan, N. (Rheedea, 2002)
The Poaceous species Ischaemum keralensis Sreek. et al. is merged with I. copeanum Sreek. et al. The original description of this highly variable species is amended based on the study of the variants and illustrations are provided.